2019
DOI: 10.1080/15732479.2019.1594315
|View full text |Cite
|
Sign up to set email alerts
|

3D reconstruction of existing concrete bridges using optical methods

Abstract: Routine bridge inspections usually consist of visual observations. These inspections are time-consuming and subjective. There is a need to identify new inspection techniques for infrastructure that reduce traffic disturbance, and improve the efficiency and reliability of the acquired data. This study compared the performance of three different imaging technologies for the three-dimensional (3D) geometric modeling of existing structures: terrestrial laser scanning, close-range photogrammetry, and infrared scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 33 publications
1
53
0
5
Order By: Relevance
“…While the manufacturer reports a range of 4.5 m [45], the recommended distances between scan locations are 1 m for outdoor projects and 2.5 m for indoor projects [9]. While the Matterport camera has successfully been used in an outdoor setting [46,47], the interference of sunlight at the wavelengths used by the infrared camera may affect the 3D data acquisition and alignment of the scans [48,49]. In previous studies, the Matterport camera has been shown to have low accuracy in comparison to laser scanners in indoor modeling [7].…”
Section: Matterport Pro2 3dmentioning
confidence: 99%
“…While the manufacturer reports a range of 4.5 m [45], the recommended distances between scan locations are 1 m for outdoor projects and 2.5 m for indoor projects [9]. While the Matterport camera has successfully been used in an outdoor setting [46,47], the interference of sunlight at the wavelengths used by the infrared camera may affect the 3D data acquisition and alignment of the scans [48,49]. In previous studies, the Matterport camera has been shown to have low accuracy in comparison to laser scanners in indoor modeling [7].…”
Section: Matterport Pro2 3dmentioning
confidence: 99%
“…Die Erstellung von 3‐D‐Modellen von Bestandsbauwerken ist über verschiedene Techniken möglich. 3‐D‐Punktwolken können über Laserscanning, Tachymetrie oder Fotogrammetrie aufgenommen werden . Die Ableitung eines 3‐D‐Modells aus diesen Daten ist über Triangulation oder das Nachzeichnen der Querschnitte aus den Punktwolken möglich.…”
Section: Stand Der Technik Und Forschungunclassified
“…The ability to reconstruct an object in 3D is of interest for a large number of applications. Examples of three-dimensional optical imaging include the reconstruction of dental pieces for improved accuracy [1], of bridges to aid maintenance work [2], of plants/fruits to measure their growth [3] and to perform 3D mapping of the seafloor [4]. In these mentioned applications a structured light beam was used to illuminate the object of interest and the pattern that was diffusely reflected from its surface was imaged.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of the deformed light pattern, the surface of the object could be reconstructed in 3D. Generally, methods using Structured Illumination require several image acquisitions following a scanning procedure to obtain a single 3D reconstruction [1][2][3][4]. In situations where high temporal resolution is needed this multiple image acquisition is not desired, for example, when imaging fast moving and/or deforming elements such as liquid bodies.…”
Section: Introductionmentioning
confidence: 99%